Double-walled carbon nanotubes as effective conducting agents for lithium iron phosphate cathodes - Seo, Sol Bin; Song, Yeeun; Choi, Yu Rim; Kang, Min; Choi, Go Bong; Kim, Jin Hee; Han, Jong Hun; Hong, Seungki; Muramatsu, Hiroyuki; Kim, Min-Young; Lee, Doojin; Kim, Yoong Ahm (Pergamon Press Ltd., 2024)
The aim of this study was to compare the effectiveness of carbon black, single-walled carbon nanotubes (SWCNTs), and double-walled carbon nanotubes (DWCNTs) as conducting agents for lithium iron phosphate (LFP) cathodes. A water-based slurry system was employed by incorporating SWCNTs and DWCNTs with polyvinylpyrrolidone (PVP) as a dispersing agent and binder. Both SWCNTs and DWCNTs exhibited remarkable wrapping ability on the surface of LFP particles, affecting the electrical conductivity and physical properties (including adhesion and cohesion strengths) of the electrode, and then influencing the electrochemical performance of the cathode. Notably, the DWCNTs outperformed the SWCNTs as conducting agents, demonstrating higher electrical conductivity and adhesion/cohesion strengths, as well as improved rate performances. This can be attributed to the higher aspect ratio, better crystallinity, and superior mechanical strength of the DWCNTs. In situ Raman measurements conducted during the charge-discharge process showed significant changes in the Raman peaks. SWCNTs exhibited complete suppression of Raman signals upon lithiation, while DWCNTs displayed the unique ability of retaining the Raman peaks originating from the inner nanotubes, indicating the protective function of the outer tubes. These findings highlight the promising potential of the incorporation of SWCNTs and DWCNTs into cathodes, as their exceptional wrapping ability distinguishes them from multi-walled carbon nanotubes and carbon black. In particular, owing to their high aspect ratio and superior wrapping capabilities, the DWCNTs are expected to serve as effective conducting agents for advanced lithium-ion batteries.